Financial Theories with a Focus on Corporate Cash Holding Behavior: A Comprehensive Review - Muhammad Sohail Tahir; Mohd Norfian Alifiah; Muhammad Usman Arshad; Faiza Saleem (International Journal of Economics and Financial Issues, 2016)
This study reviews the role of different financial theories such as, trade off theory, pecking order theory and free cash flow theory in the decision making of corporate cash management practices. The review also shed a light on the ground breaking study of Modigliani and Miller (1958) in the field of corporate financial behavior. Majority of the literature depicts the prominence of trade off theory and pecking order theory in the cash management practices of firms. However, some empirical and theoretical studies also described the significance of free cash flow theory. Because, the managers desires to hold the distinctive power in the firm's financial and investment policies through holding higher cash level. Most importantly, based on the previous empirical findings, this study warrants the need to empirically extent the significance of financial theories in the future at sector level.